PENGARUH MANAJEMEN PERUBAHAN DAN KONFLIK TERHADAP TURNOVER INTENTION KARYAWAN PADA PT. CLIPAN TANGERANG II - Anggada Bayu Seta; Nurul Ilham; Dede Abdurohman (Universitas Pahlawan Tuanku Tambusai, 2022)
The role of human resources becomes a very important part in the organization to achieve, especially in the era of globalization when competition is so tight in business. The purpose of this study was to determine whether change and conflict management had an effect on turnover intention. This study uses a quantitative approach, by applying survey research to 50 employees of PT. Clipan Tangerang II by using statistical software SPSS 26. The results obtained that management has an effect on employee turnover intentions and conflict affects turnover intentions. Organizational achievement is certainly closely related to employee attachment to work and the organization. Keyword: Change management, Conflict and Turnover Intention